Remotely triggered morphing behavior of additively manufactured thermoset polymer-magnetic nanoparticle composite structures - Cohn, Daniel (2022)
Shape memory polymers (SMPs) based systems find technological applications in diverse areas such as soft robotics, biomedical devices and aerospace structures. The shape memory (SM) response of a custom-made, additively manufactured (AM) SMP structure can be triggered by a remote, contactless AC magnetic field, resulting in morphing of the structure. We developed AM architectures based on SM thermoset polymers loaded with magnetic nanoparticles (MNPs). Composite structures were prepared from a crosslinkable polycaprolactone dimethacrylate SMP matrix and iron oxide MNP filler. Additive manufacturing of these structures was carried out using these polymers loaded with MNP. Triggered morphing of these structures is achieved by an external alternating magnetic field; the MNP heat up, triggering the SM shape change of the polymer matrix. A variety of structures were AM by a careful choice of materials and process parameters and morphing behavior was demonstrated. This convergence of additive manufacturing technologies and structures prepared from SM thermoset polymers loaded with MNP demonstrates the feasibility of personalized, remotely triggered morphing components for advanced applications, e.g. soft robotics, biomedical devices and smart structural components in buildings.